DIFFERENT APPROACHES TO THE CLASSIFICATION OF PHRASEOLOGICAL UNITS IN ENGLISH LANGUAGE (Academicia Globe: Inderscience Research, 2022)
Questions of linguistic and speech specificity of phraseological units, their systemic nature and role in reflecting national consciousness have long attracted the attention of many researchers. Scientists pay attention to the semantic characteristic and the role of phraseological units in terms of representing the linguistic picture of the world. This article provides further information about the notion and classification of phraseological units by different scholars.